2016
DOI: 10.1016/j.bbadis.2015.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of diet and carcinogen on microRNA expression in the stem cell niche of the mouse colonic crypt

Abstract: There is mounting evidence that noncoding microRNAs (miRNA) are modulated by select chemoprotective dietary agents. For example, recently we demonstrated that the unique combination of dietary fish oil (containing n-3 fatty acids) plus pectin (fermented to butyrate in the colon) (FPA) up-regulates a subset of putative tumor suppressor miRNAs in intestinal mucosa, and down-regulates their predicted target genes following carcinogen exposure as compared to control (corn oil plus cellulose (CCA)) diet. To further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 99 publications
1
15
0
Order By: Relevance
“…Table 1 summarizes specific miRNAs modulated by a combination fish oil and pectin diet with respect to their validated mRNA target genes. Surprisingly, miR-21 was decreased by the combination diet compared to the control diet (189, 190). This is noteworthy because, as previously noted, miR-21 is a well-known oncogenic miRNA, and its validated targets, PDCD4 and PTEN, are known tumor suppressor genes (9, 135, 229).…”
Section: Effects Of N-3 Pufa Fiber and Curcumin On Noncoding Micrornasmentioning
confidence: 85%
See 1 more Smart Citation
“…Table 1 summarizes specific miRNAs modulated by a combination fish oil and pectin diet with respect to their validated mRNA target genes. Surprisingly, miR-21 was decreased by the combination diet compared to the control diet (189, 190). This is noteworthy because, as previously noted, miR-21 is a well-known oncogenic miRNA, and its validated targets, PDCD4 and PTEN, are known tumor suppressor genes (9, 135, 229).…”
Section: Effects Of N-3 Pufa Fiber and Curcumin On Noncoding Micrornasmentioning
confidence: 85%
“…For example, repression of the translation of select miRNAs in stem cells and differentiated daughter cells has been shown to be a means of regulating stem cell renewal and differentiation (56, 66, 94). Although evidence supports the beneficial effects of certain dietary components on suppression of colon cancer cells (46, 190), a comprehensive, comparative analysis of the effects of these dietary agents on colonic stem cells has not yet been conducted (189). …”
Section: Effects Of N-3 Pufa Fiber and Curcumin On Noncoding Micrornasmentioning
confidence: 99%
“…Furthermore, combination of dietary fish oil and fermentable fiber pectin led to up-regulation of several miR, including miR-19b, miR-26b, and miR-203, whose validated targets (PDE4B, PTK2B, TCF4, IGF1R, and BACE1) promote tumorigenesis, as compared to control corn oil diet. Surprisingly, miR-21 was increased by the combination diet as compared to the control diet (Shah et al, 2011, 2016). …”
Section: Protective Effectsmentioning
confidence: 86%
“…This led to enhanced expression of CDKN1C (p57 KIP2 ; Hu et al, 2015), one of the cyclin-dependent kinase inhibitors found dysregulated in cancer (Kavanagh and Joseph, 2011). As mentioned above, SCFA and fish oil ω3 PUFA worked coordinately in vivo to protect against colon tumorigenesis by modulating miR (Davidson et al, 2009; Shah et al, 2011, 2016). Collectively, these findings uncovered a novel mechanism whereby butyrate suppresses onco-miR biogenesis, promotes apoptosis and diminishes CRC cell proliferation.…”
Section: Protective Effectsmentioning
confidence: 92%
“…It has been shown that miRNA are critical for the appropriate regulation of fundamental cellular pathways and as such have been implicated in a range of processes that if incorrectly regulated can lead to diseases such as cancer (2,5,7) . Furthermore, dietary factors are thought to influence miRNA levels and potentially activate abnormal cellular pathways in cancer development (26)(27)(28)(29)(30)(31) , and Se status has been shown to affect miRNA levels in the CaCo-2 cell line (32) . However, the effect of dysregulated miRNA expression, due to a low-Se environment, on key pathways in cancer development and progression is unclear.…”
mentioning
confidence: 99%